Infection rate of Enterobius vermicularis ( Pinworm) among school children in Sebha, Libya. - Rugaia, M. A. Elsalem; Lamah I. A. Imhmmed; Mabrouka M. Lahwal; Isra M. Abdulla; Somaya Yousef. (Sirte Journal of Medical Sciences, 2023)
Helminthic infections caused by Enterobius vermicularis have a cosmopolitan character and most often affect the paediatric pre-school and school age population. This helminth is the most frequent in Libya, but it is as yet unrecognized, probably due to parasitological laboratories not being consulted. The cellophane scotch tape method was used to investigate the presence of E. vermicularis eggs in 115 specimens. The overall infection of this parasite was 11.3%.Out of 115 school children (62 boys and 53 girls) nine (14.51%) boys, and four (7.54%) girls, were found infected with this parasite. There was a significant difference (X2=5.39, P=0.022) between both genders. Highest prevalence rate (13.84%), was found among 8 to10 years old age group. The adhesive scotch tape method appeared to be sensitive and appropriate choice to diagnose infection of E. vermicularis..